Management Research on Reciprocity: A Review of the Literature - Markus Göbel; Rick Vogel; Christiana Weber (BuR - Business Research, 2013)
Although reciprocity is fundamental to all social orders, management research offers few reviews of the concepts theoretical origins and current applications. To help bridge this gap, we elucidate the dominant understandings of reciprocity, ask which areas of research emerge from them, and explore how they interconnect. Our bibliometric methodology detects four clusters of management research on reciprocity. Across these clusters, authors subscribe mainly to substantialist ontology, marginalize morally oriented motives consistent with relational ontology, and largely assume that benefit-oriented motives underlie reciprocity. We outline the advantages of a moral-oriented relationalist concept of reciprocity and discuss potential areas for its development in management research.
urn:nbn:de:0009-20-36451
Keywords: 650; benefit orientation; bibliographic coupling; bibliometrics; citation analysis; morality; network analysis; ontology; practice theory; reciprocity; social exchange; Austauschtheorie (Soziologie); Bibliometrie; Operations Research; Wissenschaftsforschung